Communicative Planning As Institutional Capacity Building: From Discourse/Network To Opportunity - Delik Hudalah (Diponegoro University, 2013)
The paper redefines the ideas about communicative planning as not only participatory and democratic practice but also capacity building oriented toward the improvement of governance styles and consciousness. So far capacity building has focused on the exploitation of social resources internal to actors. These internal resources include knowledge (argumentation, debate, discourse formation etc) and relational (network, coalition, alliance etc) building. The paper argues that in dealing with very complex planning problems characterized by fragmented and uncertain institutional systems, the internal resources need to be coupled with the exploration of resources external to actors, namely the political opportunity structure and moment of opportunity. The analysis implies that the performance of communicative decision-making process as capacity building can be assessed in three aspects: strategic and inclusive actors’ involvement, the building of actors’ awareness on neglected but important planning issues and agendas, and consistency and deliberation in realizing and delivering agreed planning ideas, frameworks and decisions.